Should a physician use the Beers criteria when prescribing direct oral anticoagulants to elderly patients? - N. M. Vorobyeva; I. P. Malaya; V. D. Zakiev; O. N. Tkacheva (Рациональная фармакотерапия в кардиологии)
The Beers Criteria are a tool for optimizing pharmacotherapy in elderly patients, containing information on potentially inappropriate drugs, which is only advisory in nature and is not mandatory for use in Russian Federation. In the updated version of the Beers Criteria from 2023, the expert opinion on rivaroxaban has changed — instead of "use with caution", as stated in the previous document from 2019, the experts now believe that "long-term treatment with rivaroxaban in non-valvular atrial fibrillation (AF) and venous thromboembolic complications (VTE) should be avoided in favor of safer alternative anticoagulants". This statement is based on moderate-quality evidence obtained from observational studies and network meta-analyses, which are significantly inferior to randomized controlled trials and have numerous limitations. The available evidence base for the use of rivaroxaban in elderly patients with AF and VTE and critical comments on the Beers criteria methodology, indicate the recommendations of the American Geriatrics Society experts regarding direct oral anticoagulants (DOAC) should be treated thoughtfully and carefully. When choosing a DOAC in elderly patients with AF or VTE, one should primarily focus on current clinical guidelines mandatory for use in Russian Federation, and on the data of studies that studied the efficacy and safety of specific DOACs in this category of patients. Rivaroxaban is a well-studied anticoagulant in elderly patients with AF and VTE, since its efficacy and safety have been established in RCTs and specially designed multicenter prospective observational studies with a fairly high quality of evidence. Based on this, rivaroxaban is a justified treatment option for elderly and senile patients with AF or VTE.